Typing carbonate reservoir rocks using the accumulated correlation method and individual probabilistic models on the example of fields in the Yuzhno-Khoreyverskaya area - Ivan S. Putilov; Tatyana A. Zhemchugova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. The need to understand a complex carbonate object for a confident prediction of the properties of reservoir rocks, to describe with mathematical tools the patterns of changes in the structure of void space and to improve methods for typing reservoir rocks when interpreting petrophysical data obtained in laboratory conditions. Aim. Integrated application of individual probabilistic models and the accumulated correlation method to describe patterns of changes in the structure of void space and typification of carbonate reservoir rocks, taking into account the results of facies and lithological analysis using the example of the Trans-Don carbonate reef deposits of the Famennian stage of the Upper Devonian of the South Khoreyversky area. Methods. Mathematical modeling, methods of mathematical statistics for the analysis of experimental data and for describing patterns. Results and conclusions. The authors have assessed the statistical distinguishability of core samples based on the Student's t-test and Fisher's F-test, grouped by type of void space, lithology and facies. They studied the patterns of changes in the structure of the void space using individual probabilistic models of the open porosity coefficient, taking into account geological factors and accumulated correlation graphs. Additionally, the authors assessed the nonlinearity of trends in individual probabilistic models, which made it possible to identify subzones on the accumulated correlation graph, as well as describe slope angles and other effects. Based on the results of linear discriminant analysis, statistically significant functions were obtained for typing samples according to the type of void space. Based on the results of multiple regression analysis of open porosity for carbonate reservoir rocks, statistically significant multiple regression models of the separate and combined influence of different geological factors on porosity were obtained. Based on the conducted research and comprehensive analysis, it was established and confirmed that the integrated use of accumulated correlation and individual probabilistic models is an informative analytical and mathematical tool for typing carbonate reservoir rocks and assessing the connections and mutual influence of geological factors in the rock.